Justification of metformin hydrochloride biowaiver criteria based on bioequivalence study - Homšek, Irena; Parojčić, Jelena; Dačević, Mirjana; Petrović, Ljiljana; Jovanović, Dušan (Arzneimittelforschung, 2010)
The Biopharmaceutics Classification System (BCS) represents the framework for predicting the intestinal drug absorption based on its solubility and intestinal permeability. Recent research has lead to the use of in vitro tests to waive additional in vivo bioequivalence studies for some pharmaceutical products (i. e. biowaiver). The current regulations permit waivers for BCS Class I (highly soluble/highly permeable) drug substances, which represent up to 25 % of the drugs. Efforts in both the science and regulatory bodies are being made to extend biowaivers to certain Class II and III products, which would represent more than 50 % of all drugs coming to the market. The aim of this study was to investigate the influence of experimental conditions on metformin hydrochloride (CAS 1115-70-4) release from two immediate-release tablet formulations with proven bioequivalence and justify the biowaiver request for dissolution profile similarity in three pH media.The results obtained indicate that differences in drug dissolution observed in vitro were not reflected in vivo. Such data support the existing idea that BCS Class III drugs are eligible biowaiver candidates, even if a very rapid dissolution criterion is not fulfilled.
Keywords: Antihyperglycemic drug; BCS Class III drugs; CAS 1115-70-4; In vitro - in vivo correlation; Metformin hydrochloride, bioequivalence, dissolution, immediate-release